Penerapan Metode Kaisa Dalam Meningkatkan Kemampuan Menghafal dan Menerjemahkan Ayat-Ayat Al-Qur'an - Permata Sari, Deva; Mardeli, Mardeli; Fitri, Emilia (PAI RAFAH, 2025)
This study aims to determine whether the kaisa approach has a significant effect on the ability of SDN 54 Palembang's grade II pupils to comprehend and analyze Qur'anic passages in Islamic Religious Education classes. The kaisa method assists individuals in learning and understanding the meanings of the Qur'anic verses by employing limb movements that are specific to each verse. Quantitative research with an experimental foundation falls under this heading. Its research methodology was a single group pre-test post-test design. This study included a sample of 28 students from SDN 54 Palembang's class IIB. The data was gathered through observation, documenting, and testing. The data analysis method uses both normality and hypothesis testing. Students' ability to memorize and translate Qur'anic verses was 4 individuals, or 14% of the high category, 17 people, or 61% of the medium category, and 7 people, or 25% of the poor category, with a mean score of 62.14 before the kaisa method was used. Following the application of the kaisa method, five individuals, with a mean score of 85.71, fell into the poor category for the ability to memorize and translate the verses of the Qur'an, while six students, or 21% of the total, fell into the high group and 17 individuals, or 61%, into the medium category. The paired sample t-test findings show that when the Sig value (2-tailed) is 0.000, which means 0.000 <0.05, Ho is rejected and Ha is accepted. During Islamic Religious Education and Cultivation, class II pupils at SDN 54 Palembang showed that using the kaisa approach improved their ability to memorize and translate Qur'anic passages.